Enhancement of mechanical properties and corrosion resistance of bainitic elastic rail clip (ERC) with finer microstructural morphology. (December 2022) - Neetu,; Bhagyaraj, J.; Mukherjee, S.; Sangal, S.; Mondal, K.
Abstract: Present work discusses the enhancement of hardness and tensile strength of the existing quenched and tempered elastic rail clip (ERC) by modifying the microstructure to bainite via austempering at 300ºC with various holding durations of 15 min, 30 min and 60 min after austenitization at 950 ºC. Further, the corrosion resistance of these austempered ERC specimens evaluated in freely aerated 3.5 wt% NaCl solution with the help of electrochemical tests (electrochemical impedance spectroscopy, linear polarization and potentiodynamic polarization) is better than the as-received (existing) ERC specimen with tempered martensitic structure. The variation in corrosion rate of the austempered ERC specimens is attributed to the finer galvanic couple formed between the ferrite and cementite phases in the bainitic structure. Further rust analysis using scanning electron microscopy and Raman spectroscopy after electrochemical tests shows the presence of various rust phases such as α-FeOOH, β-FeOOH, γ-FeOOH and α-Fe2 O3 . The higher protective ability index (α/γ *) as determined by the relative fraction of protective α-FeOOH and α-Fe2 O3 with dissolving β-FeOOH and γ-FeOOH phases of the austempered ERC specimen attributed further to their higher corrosion resistance. Graphical Abstract: ga1 Highlights: Effect of austempering on mechanical and corrosion behavior of elastic rail clip is studied. Tensile strength of the austempered steel increases with increase of isothermal holding time. Corrosion rate decreases with increase of bainite fraction in the austempered steel. Rust constituents uniquely controls the corrosion of bainitic elastic rail clips. High C at edge of RA near to bainitic ferrite results in higher dissolution of interface.